Stigma and discrimination in individuals with severe and persistent mental illness in an assertive community treatment team: Perceptions of families and healthcare professionals. (November 2019) - O'Reilly, Claire L; Paul, Diane; McCahon, Rebecca; Shankar, Sumitra; Rosen, Alan; Ramzy, Thomas
Aim: To explore family member and staff perceptions of clients' experiences of stigma and discrimination, in those living with severe and persistent mental illness in an Assertive Community Treatment Team. Method: This qualitative study used the Discrimination and Stigma Scale to conduct structured face-to-face and telephone interviews of family members and healthcare professionals, working with the Assertive Outreach Team (AOT) (an Assertive Community Treatment Team) of a northern inner suburban catchment of Sydney, New South Wales, Australia. Results: Forty-one people participated in the study (23 AOT clinical staff members and 18 family members). Family and clinical staff commonly reported stigma and discrimination amongst their relatives and clients, respectively. Four overarching themes emerged from the data: (1) appearance and behaviour, (2) avoidance and being shunned, (3) key areas of life affected by discrimination and (4) impacts of discrimination and skills to cope with discrimination. Conclusion: Reports of stigma and discrimination were common, yet varied between groups with clinical staff commonly witnessing experiences and impacts of discrimination in everyday life, with families' reports being substantially less. Due to the strong advocacy and support provided by the AOT model, clinical staff often buffered experiences of stigma and discrimination. Further research is needed to explore effective interventions to reduce experiences of discrimination in this population group.